Analisis Bauran Pemasaran terhadap Keputusan Pembelian Produk Caldonat di Rumah Sakit Annisa Cikarang - Sarmin Sarmin; Siti Nurhalisa; Iin Aini (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the effect of product, price, promotion, and place on purchasing decisions for Caldonat products. The research uses a quantitative approach with an associative type, as it seeks to examine the relationship between multiple variables. The data collection technique used is a questionnaire distributed directly to respondents. The sampling technique applied is non-probability sampling using the incidental method, with a total sample of 100 respondents. Data analysis techniques include multiple linear regression analysis, classical assumption tests (normality, linearity, multicollinearity, and heteroscedasticity), and hypothesis testing, both partially (t-test) and simultaneously (F-test). Data processing was carried out using SPSS version 29.0.The results show that product, price, promotion, and place variables have a positive and significant influence on purchasing decisions, both partially and simultaneously. Among them, the distribution variable has the most dominant effect, with a t-value of 2.893 > t-table value of 2.093 and a significance level of 0.005 < 0.05. Simultaneously, the F-value is 17.695 > F-table 2.71, with a significance level of 0.000. The coefficient of determination (R²) is 40.3%, indicating that the four variables explain 40.3% of the purchasing decision, while the remaining 59.7% is influenced by other factors not examined in this study